KAJIAN TERHADAP GANTI RUGI TANAH PADA PROYEK PEMBANGUNAN TOL KUNCIRAN-BANDARA SOEKARNO HATTA - Rozi, Ahmad (Gapenas Publisher, 2025)
This research was carried out to see whether the construction of the Kunciran – Soekarno Hatta Airport Toll Road was in accordance with the land acquisition law or vice versa. This study aims to analyze the implementation of land compensation in the Kunciran-Soekarno-Hatta Airport toll road construction project using quantitative methods. The main focus of the research is to identify the extent to which the implementation of land compensation is in accordance with applicable regulations and how regulatory uncertainty affects the process. Data is collected through surveys of affected parties, such as land owners, as well as analysis of documents and official reports related to compensation policies. The results of the study show that the implementation of land compensation is often only a formality, with a lack of transparency and accuracy in determining the value of compensation. This is due to uncertainty in the regulations that govern the compensation mechanism and criteria, thus causing dissatisfaction among the affected communities. The study highlights the need for stricter revision of policies and regulations as well as a more participatory process to ensure fairness for all affected parties in strategic infrastructure development.